1992
DOI: 10.1111/j.1651-2227.1992.tb12074.x
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis: haematological status and the absorption of vitamin B12 and folic acid

Abstract: The haematological status, as well as the fractional absorptions of folic acid (FAFol) and vitamin B12 (FAB12) were studied in 29 children aged 0.7-13.5 years (mean 3.3 years) with chronic diarrhoea due to giardiasis. Small intestinal biopsies revealed mucosal damage in 20 children; the biopsies of the remaining nine children were normal. At the initial investigation the FAFol and FAB12 values were below normal in approximately one-sixth and one-third of patients, respectively. Bacterial overgrowth of the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…Gastric bypass surgery, gluten enteropathy, some drugs and Helicobacter pylori gastritis are common causes of vitamin B12 malabsorption 1,5,16,[21][22][23][24][25][26][27][28][29] Although only 85 patients underwent endoscopic evaluation in our study, Helicobacter pylori positive gastritis rate was found quite frequently (77.6%), which is concordant with the findings of a previously published paper. 25 In that article, authors noted that Helicobacter pylori IgG values were not statistically different between the patients with low and normal vitamin B12 levels, although they were slightly higher in low B12 group.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Gastric bypass surgery, gluten enteropathy, some drugs and Helicobacter pylori gastritis are common causes of vitamin B12 malabsorption 1,5,16,[21][22][23][24][25][26][27][28][29] Although only 85 patients underwent endoscopic evaluation in our study, Helicobacter pylori positive gastritis rate was found quite frequently (77.6%), which is concordant with the findings of a previously published paper. 25 In that article, authors noted that Helicobacter pylori IgG values were not statistically different between the patients with low and normal vitamin B12 levels, although they were slightly higher in low B12 group.…”
Section: Discussionsupporting
confidence: 81%
“…The most common reason accounting for deficiency is inadequate intake. [1][2][3][4][5]9,11,12,15,[20][21][22][23][24][25][26][27][28][29] Our study also displays the importance of inadequate intake of Vit B12-rich food items in the occurence of serum Vit B12 deficiency. As well known, dietary deficiency is most commonly observed among strict vegetarians, alcoholics and elderly.…”
Section: Discussionmentioning
confidence: 85%
“…Low vitamin B 12 levels have been seen in cases of infection with Giardia lamblia, Plasmodium falciparum, Diphyllobothrium latum and Strongylloides stercolaris [20,21]. Hjelt et al [22], in 1992, noted an abnormal fractional absorption of vitamin B 12 and folic acid in children with chronic diarrhea due to giardiasis. In the initial investigation, these values were below normal in one-third and one-sixth of patients, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Cobalamin deficiency is reported to be common also in India (Jathar et al, 1970;Kumar et al, 1989). In addition, malabsorption due to intestinal infections (Casterline et al, 1997;Hjelt et al, 1992) and the increased requirements during pregnancy (Allen, 1994) may represent possible causes of cobalamin deficiency. In many cases, it is most likely a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%